The Impact of Work Teams on Improving Organizational Performance: A Field Study of Organizations in Amman, Cairo, and Baghdad: Dampak Tim Kerja terhadap Peningkatan Kinerja Organisasi: Studi Lapangan pada Organisasi di Amman, Kairo, dan Baghdad - Husam Raad Jasim (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Organizations increasingly rely on collaborative work structures to achieve institutional goals and maintain productivity in dynamic environments. Specific Background: Teamwork is widely recognized as a managerial approach that enables employees to share knowledge, coordinate tasks, and address organizational challenges collectively. Knowledge Gap: Despite the widespread application of teamwork in organizations, empirical understanding of its role in shaping organizational performance across different institutional contexts remains limited. Aims: This study examines the relationship between work teams and organizational performance in organizations located in Amman, Cairo, and Baghdad. Results: Using a theoretical framework and a field survey based on questionnaire data, statistical analysis revealed a significant relationship between teamwork practices and organizational performance indicators. The findings show that teamwork facilitates knowledge exchange, strengthens trust among employees, and supports collaborative problem solving within organizations. Regression analysis indicates that teamwork explains a considerable proportion of variation in organizational performance. Novelty: The study provides empirical evidence demonstrating the managerial role of teamwork as a strategic organizational practice within different institutional environments. Implications: The findings highlight the importance of fostering collaborative cultures, supporting team formation, and encouraging participation among employees to strengthen organizational productivity and coordination. Keywords: Teamwork, Organizational Performance, Work Teams, Organizational Flexibility, Human Resource Management Key Findings Highlights Collaborative work structures support knowledge sharing among employees Organizational cooperation strengthens trust and communication within teams Team-based practices contribute to higher levels of employee productivity